Experimental and simulation study of biodiesel combustion in a microturbine - Tan E.S.; Palanisamy K. (2023)
Biodiesel, produced from the transesterification of renewable sources is one of the answers to today's energy scarcity and environmental challenge. The success of biodiesel in transportation sector has shown that there is great potential for biodiesel to be used as an alternative fuel for gas turbine and microturbine. This paper presents the experimental and simulation results of performance test conducted in a 30kW microturbine to replicate the combustion of biodiesel derived from Waste Cooking Oil originated from palm oil source. The test was conducted using biodiesel, distillate and their blends up to a maximum of 20 percent biodiesel concentration. The study shows that the thermal efficiency and combustion efficiency increases when biodiesel blends increased. The fuel consumption for biodiesel blends are marginally higher compared to neat distillate. From the data obtained, a numerical analysis was conducted to simulate the thermal efficiency computation for biodiesel blends beyond 20 percent concentration. The predicted results showed that the thermal efficiency for B100 increased by 2 percent for the entire rated power output. This finding shows a promising potential for the application of biodiesel as an additive to gas turbine liquid fuel, to increase efficiency, in line with existing power augmentation works. Copyright 2008 by ASME.